BS EN 4165-016. Aerospace series. Connectors, electrical, rectangular, modular. Operating temperature 175 °C continuous. Part 016. Double oval chimney for accessory (1 per 2 modules). Product standard (10th December 2021) - British Standards Institution,
No abstract available